How the velocity and the forewarning of a target, can affect the relation of eye and hand reaction times - Sanegre, M. T.; Valls-Solé, J.; Castellote, J.M.; Contreras, R. (International Journal of Computer Science in Sport, 2002)
Moving the eyes towards a target is required for an accurate performance in visually-guided hand movement tasks such as grasping an object or stopping a ball. Saccadic eye movements (EM) are usually much quicker than reaching hand movements (HM). Onset of EM was found to precede onset of HM by as much as 100 ms in a pointing task (Prablanc et al., 1979). However, eye and hand movements are not always well correlated (Gielen et al., 1984; Carnahan and Marteniuk, 1991; Biguer et al., 1982; Prablanc et al., 1981). Intercepting a target moving at high speed can be made without even foveating at the target, as in many sports and games. How the motor commands required for an accurate arm movement are constructed from the limited amount of visual information on target position obtained in these instances is not known. Target velocity is an important factor for selection of the type of motor strategy to be used for target interception.